(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This work examines the problem-based learning method as an active approach that allows students to encounter real or simulated problems, contributing to the development of critical thinking and creative abilities. As a practical example, the use of the “literary evolution” method in the literature curriculum is described, where students explore the influence of classical works on modern literature.